2011
DOI: 10.4103/0976-237x.79296
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of total antioxidant capacity levels in saliva of caries-free and caries-active children

Abstract: Background and Objectives:The purpose of this study was to evaluate total antioxidant levels in caries-free and caries-active children.Materials and Methods:The present study included one hundred and twenty healthy children who were divided into two groups; Group I and Group II, comprising of age groups 7 to 10 years and 11 to 14 years. respectively. Both the groups were then sub-divided equally according to gender. They were further divided into caries-free and caries-active children with 15 children in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 8 publications
1
28
2
Order By: Relevance
“…There are also limited studies on salivary TAC in dental caries [Tulunoglu et al, 2006;Hegde et al, 2009;Preethi et al, 2010;Dodwad et al, 2011;Kumar et al, 2011;Mahjoub et al, 2014].…”
mentioning
confidence: 99%
“…There are also limited studies on salivary TAC in dental caries [Tulunoglu et al, 2006;Hegde et al, 2009;Preethi et al, 2010;Dodwad et al, 2011;Kumar et al, 2011;Mahjoub et al, 2014].…”
mentioning
confidence: 99%
“…These findings were in agreement with Roa et al, [50] who found no difference in total protein levels between caries-free and caries-active adults. On contrast, Preethi et al, and Dodwad et al, [18,51] have shown that total proteins were significantly higher in caries active in comparison to caries free children. Salivary α-defensin is part of antimicrobial innate immunity.…”
Section: Discussionmentioning
confidence: 88%
“…[1]The reason for increased TAC in caries active tribal children could be : It has been seen that salivary peroxidase system constitutes to be one of the major salivary antioxidant systems. Salivary peroxidase brings about the control of oral bacteria that form dental plaque, to imbalance in the ecology, which lead to dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Results of studies on TAC Tulunoglu et al [9] Total antioxidant values were higher in caries active groups Uberos et al [13] Total antioxidant capacity of the saliva of patients with caries in deciduous teeth was greater than among those without caries Prabhakar et al [14] Total antioxidant capacity of saliva increased significantly in caries active children Hegde et al [15] Total antioxidant capacity of saliva increased in children with caries Preethi et al [10] Total antioxidant capacity of saliva increased in caries active children Kumar et al [16] TAC of saliva increased in children with Severe early childhood caries and increasing prevalence of dental caries predisposes to the increase in TAC of saliva Dodwad et al [1] Total antioxidant capacity of saliva increased significantly in cariesactive children when compared to caries-free children Hegde et al1 [7] TAC level increases with increase in severity of caries Ahmadi-Motamayel et al [18] TAC was significantly higher in the saliva of caries active group relative to the caries free subjects Mahjoub et al1 [9] TAC levels and salivary total protein increased in children with severe early childhood caries compared with caries-free children Pandey et al [20] Total antioxidants in saliva increased with caries activity Muchandi et al [21] Salivary TAC increases in patients with early childhood caries Silva et al [22] Salivary Total Antioxidant capacity was higher in children with early childhood caries as compared to caries free children …”
Section: Name Of the Authormentioning
confidence: 99%
See 1 more Smart Citation